Conductive Hearing Loss Cases Tested at the AIISH - Mythili MA (Journal of All India Institute of Speech and Hearing, 1970)
A conductive hearing loss is one in which effective transmission  of sound into the inner ear has met some type of interference at the external canal, tympanic membrane, ossicular chain, middle ear cavity, round window or oval window. Any dysfunction of the outer ear or middle ear in the presence of a normal inner ear is termed a conductive impairment of hearing. Difficulty is not with the perception of sound but with the conduction of sound to the analyzing system. By definition a 'pure' conductive loss  result from pathology or mal-functioning of the outer or middle ear with a normal inner ear.This means that a patient with a conductive loss should present an audiogram showing loss by air conduction and normal hearing by bone conduction.